2021
DOI: 10.1039/d1ja00149c
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticles in analytical laser and plasma spectroscopy – a review of recent developments in methodology and applications

Abstract: The present review attempts to comprehensively overview the progress in the field of nanoparticle-related analytical laser and plasma spectroscopy research, focusing on the results of the past decade. The discussion...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 593 publications
(576 reference statements)
0
14
0
1
Order By: Relevance
“…Nanoparticles were the topic of a comprehensive review (290 references) that covered 57 advances in methods for determination of their abundance, morphology, composition and structure in water, soil, sediment and biological samples. Laser- and plasma-based approaches for NP characterisation were included 117 in a broader review (596 references) that also covered monitoring of NP synthesis and the use of NPs for signal enhancement.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Nanoparticles were the topic of a comprehensive review (290 references) that covered 57 advances in methods for determination of their abundance, morphology, composition and structure in water, soil, sediment and biological samples. Laser- and plasma-based approaches for NP characterisation were included 117 in a broader review (596 references) that also covered monitoring of NP synthesis and the use of NPs for signal enhancement.…”
Section: Analysis Of Soils Plants and Related Materialsmentioning
confidence: 99%
“…Galbács et al 120 reviewed recent developments in methods and applications utilising NPs. Connections between nanoparticles and laser and plasma spectroscopy were discussed in three major areas, including the monitoring of NP synthesis, characterisation and plasmonic signal enhancement.…”
Section: Laser Induced Breakdown Spectroscopy (Libs)mentioning
confidence: 99%
“…24 In 2019, this group, one of the most proliferic groups in the field, also wrote a review on microfluidic chip-ICP-MS for trace element and their species analysis in cells. 8 [26][27][28] In our previous studies, we demonstrated that not only single-component 4 or homogenous (random) alloy spherical NPs can be analyzed, and additional information, such as the structure and aspect ratio, as well as the porosity can also be obtained by the spICP-MS method. [29][30][31] spICP-MS analysis takes only a couple of minutes, and the required particle concentration is small (ca.…”
Section: Introductionmentioning
confidence: 99%
“…As it was shown in recent years in the literature, through the evaluation of the signal histograms, the technique can provide information about the presence, size distribution, number concentration, elemental or isotopic composition of nanoparticles. [26][27][28] In our previous studies, we demonstrated that not only single-component or homogenous (random) alloy spherical NPs can be analyzed, and additional information, such as the structure and aspect ratio, as well as the porosity can also be obtained by the spICP-MS method. [29][30][31] spICP-MS analysis takes only a couple of minutes, and the required particle concentration is small (ca.…”
Section: Introductionmentioning
confidence: 99%